THE EFFECT OF RED DRAGON FRUIT PEEL EXTRACT ADMINISTRATION IN MICE (Mus musculus) ABSOLUTE MONOCYTE COUNTS IN PERIAPICAL RADIOGRAPHY EXPOSURE - Nurlailatul Rahmah; Didit Aspriyanto; R. Harry Dharmawan Setyawardhana (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Exposure to periapical radiographic X-ray radiation can indirectly affect biological material which will trigger the formation of free radicals. An imbalance in the level of free radicals causes oxidative stress. To reduce it, additional antioxidants obtained from nature are needed. Natural antioxidants can be obtained from the peel of red dragon fruit which the function is to reduce the presence of free radicals. Objective: to analyze the effect of red dragon fruit peel extract administration in mice absolute monocyte counts in periapical radiographic exposure. Method: This study was a true experimental design with a post-test only with control group design. The research sample used 24 mice. Samples were divided into 6 groups: the control group was not given with the treatment, P1 to P4 group were given red dragon fruit peel extract at a dose of 100 mg / kg bb and exposed to radiation with different exposures, P5 group was given red dragon fruit peel extract but not exposed. P1 group was exposed to 1 dose (0.63 mGy), P2 group was exposed to 4 doses (1.66 mGy), P3 group was exposed to 8 doses (4.37 mGy), and P4 group was exposed to 12 doses (8.19 mGy). Results: This study showed that there were changes in the number of monocytes in all groups. The Games Howell test showed that the P1 group had a significant difference compared to the P4 and P5 groups. Conclusion: There is an effect of red dragon fruit peel extract administration in mice absolute monocyte counts in periapical radiographic exposure.